1997
DOI: 10.1089/neu.1997.14.637
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin in the Management of Elevated Intracranial Pressure: A Review

Abstract: Elevated intracranial pressure occurs frequently in patients with severe head injury. A number of studies in recent years suggest that indomethacin may be useful in the management of elevated intracranial pressure. Indomethacin acts primarily by reducing cerebral blood flow and decreasing cerebral edema following head injury. This review summarizes the basic and clinical studies of the effects of indomethacin on cerebral blood flow, brain edema, and intracranial pressure. The pharmacology of indomethacin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 86 publications
0
24
0
Order By: Relevance
“…17 The dose of indomethacin used in this study has been shown to affect CBF without concomitant changes in neuronal activity, as reflected by local cerebral glucose utilization. 21 However, the mechanisms responsible for indomethacin-mediated cerebral vasoconstriction are complex and include non-prostaglandin-related pathways.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…17 The dose of indomethacin used in this study has been shown to affect CBF without concomitant changes in neuronal activity, as reflected by local cerebral glucose utilization. 21 However, the mechanisms responsible for indomethacin-mediated cerebral vasoconstriction are complex and include non-prostaglandin-related pathways.…”
Section: Discussionmentioning
confidence: 81%
“…17,24 However, we do not recommend the use of indomethacin to prevent the development of brain edema and cerebral hyperemia in human FHF. The administration of the drug at an early stage of the neurologic picture in FHF could result in renal vasoconstriction and pose risks of gastrointestinal hemorrhage.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…10 It was therefore suggested that alternative treatments should be developed for GC use in the management of patients with a solid tumor, to take care of inflammation and edema, nausea and emesis. 5,10 Several agents have been considered for the non-steroidal treatment of brain edema, including indomethacin, 5,11,12 which inhibits both COX-1 and COX-2, boswellic acid 13 and celecoxib. 14 Celecoxib is a selective non-steroidal anti inflammatory inhibitor of the COX-2 enzyme and inhibits edema development after experimental brain bleeding.…”
Section: Introductionmentioning
confidence: 99%